2023
DOI: 10.1101/2023.11.22.23298843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-reported decreases in the purchases of selected unhealthy foods resulting from the implementation of warning labels in Mexican youth and adult population

Alejandra Contreras-Manzano,
Christine M. White,
Claudia Nieto
et al.

Abstract: BackgroundFront-of-package nutritional warning labels (WLs) are designed to facilitate identification and selection of healthier food choices. We assessed self-reported changes in purchasing different types of unhealthy foods due to WLs in Mexico and the association between the self-reported reductions in purchases of sugary beverages and intake of water and sugar-sweetened beverages.MethodsData came from 14-17 year old youth (n=1,696) and adults ≥18 (n=7,775) who participated in the Mexican arm of the 2020-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This might suggest that participants from Mexico, despite having been exposed to warning labels for two years, have not learned to adjust their food choiceswhich is also supported by the fact that they did not necessarily make healthier choices than participants from the other countries. This would, however, be at odds with initial evaluations of the real-world implementation of warning labels in Mexico, where a substantial number of respondents indicated to have changed their food choice patterns post-implementation (45). Thus, results could also be interpreted in a different manner: First, they might indicate that FOPNL are in fact easily and intuitively understood, and minimal information is required for individuals to be able to make use of the labels (46).…”
Section: Comparisons Across Countriesmentioning
confidence: 95%
“…This might suggest that participants from Mexico, despite having been exposed to warning labels for two years, have not learned to adjust their food choiceswhich is also supported by the fact that they did not necessarily make healthier choices than participants from the other countries. This would, however, be at odds with initial evaluations of the real-world implementation of warning labels in Mexico, where a substantial number of respondents indicated to have changed their food choice patterns post-implementation (45). Thus, results could also be interpreted in a different manner: First, they might indicate that FOPNL are in fact easily and intuitively understood, and minimal information is required for individuals to be able to make use of the labels (46).…”
Section: Comparisons Across Countriesmentioning
confidence: 95%
“…In all 3 cases, weight reduction is simulated for 1 year, although the nonlinear equation used in all studies suggests that further impacts on body weight after the first year of simulation are to be expected [40]. Empirical evidence from an online survey in adolescents aged 13 to 17 years in Mexico showed a reduction of 38.7% in the purchase of NEDFBs after the implementation of the front-of-package labeling [41]. However, the relative reduction does not allow us to quantify the reduction in kcal to properly compare the results with our study.…”
Section: Plos Medicinementioning
confidence: 99%
“… 14 A survey found that 44.8% of adults reported buying less unhealthy food because of front-of pack labelling, although the survey is not nationally representative. 15 Still, it is unknown whether an earlier implementation of these measures could have changed the COVID-19 epidemic impact in Mexico.…”
Section: Introductionmentioning
confidence: 99%